2021
DOI: 10.18632/aging.203561
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits proliferation, migration, and invasion by inducing ROS-mediated apoptosis via suppression of the PI3K/Akt/mTOR signaling pathway in gallbladder cancer cells

Abstract: Background: Melatonin is an indolic compound mainly secreted by the pineal gland and plays a vital role in the regulation of circadian rhythms and cancer therapy. However, the effects of melatonin in gallbladder cancer (GBC) and the related mechanism remain unknown. Methods: In this study, the antitumor activity of melatonin on gallbladder cancer was explored both in vitro and in vivo . After treatment with different concentrations of melatonin, the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…The oncostatic effects of melatonin through its pro-oxidant actions have been widely described [ 17 , 18 , 19 , 20 , 21 , 22 , 95 ]. Its mechanism of action, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oncostatic effects of melatonin through its pro-oxidant actions have been widely described [ 17 , 18 , 19 , 20 , 21 , 22 , 95 ]. Its mechanism of action, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Various groups have, for many years, reported that high concentrations of melatonin can promote ROS generation, leading to cell death in a variety of cancers [ 17 , 18 , 19 , 20 , 21 , 22 ]; this suggests that melatonin can act as both an antioxidant and pro-oxidant in human cell lines, depending on the concentration and treatment duration. Furthermore, numerous studies have shown that melatonin enhances the cytotoxic effects of chemotherapeutic drugs on cancer cells, depending on the dose [ 23 ], thus suggesting that melatonin increases their chemotherapeutic effect [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PI3K-AKT signals are key and powerful suppressor for oxidative stress/ROS and conversely, ROS inhibits activation of PI3K. Furthermore, ROS induces ERS in DCMs, [ 31 – 34 , 36 , 37 , 45 ] and H19 indirectly activates PI3K by sponging miR-140-5p. Our results showed that H19 significantly increased the activation of PI3K and Nrf2 and thus decreased the expression of NOX-2/-4, as well as under high glucose conditions, and unfolded protein response’ proteins GRP-78/-94 and p-PERK and p-IRE1α, and these effects of H19 were corrected or rescued by PI3K inhibitor LY294002 ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Further experimental studies demonstrated regression of gallbladder cancer by treatment with mTOR inhibitors (47). This was independent of the typhoid carrier state and was demonstrated to be mediated through PIK3CA/AKT/mTOR pathway (48)(49)(50)(51)(52). Although the single-phase I study of docetaxel and temsirolimus was limited by severe myelosuppressive toxicity and failed to meet the objectives (53).…”
Section: Discussionmentioning
confidence: 99%